2017
DOI: 10.1111/aae.12095
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐cultural innovations of the Final Umm an‐Nar period (c.2100–2000 BCE) in the Oman peninsula: new insights from Ra's al‐Jinz RJ‐2

Abstract: The Early Bronze Age site of RJ-2, located close to the coastal village of Ra's al-Jinz on the eastern Omani coast (Niyabat Ra's al-Hadd), was the focus of archaeological investigations for over two decades. The latest campaigns of excavation unearthed an architectural complex (Building XII) dated to the very end of the Umm an-Nar period (Final UaN, c.2100-2000, previously attested on site by poorly preserved remains. This paper presents the remains explored during the most recent fieldwork, focusing on the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 10 publications
(15 reference statements)
0
19
0
Order By: Relevance
“…Notably, a number of fish preservation techniques, including sun‐drying, salting, and grilling are known in the region today (el‐Mahi, ). At both Ra’s al‐Jinz 2 and Mleiha, skeletal element patterns in the fish assemblages were also consistent with the removal of the heads and tails of fish for preservation; an abundance of head elements and tails were recovered at Ra’s al‐ Jinz 2 from large fish such as yellowfin tuna, without vertebrae present (Azzarà & de Rorre, : 21) and the fish assemblage from the Late Pre‐Islamic occupation at Mleiha is composed primarily of vertebral fragments with very few cranial elements present (van Neer, Wouters, & Mouton, : 227). At Saruq al‐Hadid, the presence of vertebrae but no cranial elements from tuna fits this pattern, and the differential representation of body parts across different fish species in the Saruq al‐Hadid assemblage likely reflects different preservation treatments for different fish.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Notably, a number of fish preservation techniques, including sun‐drying, salting, and grilling are known in the region today (el‐Mahi, ). At both Ra’s al‐Jinz 2 and Mleiha, skeletal element patterns in the fish assemblages were also consistent with the removal of the heads and tails of fish for preservation; an abundance of head elements and tails were recovered at Ra’s al‐ Jinz 2 from large fish such as yellowfin tuna, without vertebrae present (Azzarà & de Rorre, : 21) and the fish assemblage from the Late Pre‐Islamic occupation at Mleiha is composed primarily of vertebral fragments with very few cranial elements present (van Neer, Wouters, & Mouton, : 227). At Saruq al‐Hadid, the presence of vertebrae but no cranial elements from tuna fits this pattern, and the differential representation of body parts across different fish species in the Saruq al‐Hadid assemblage likely reflects different preservation treatments for different fish.…”
Section: Discussionmentioning
confidence: 75%
“…In both of the above models, the frequent identification of fish and other marine resources at Saruq al‐Hadid reflects the ubiquity and importance of fish to the societies engaging with the marine resource in the region. Indeed, researchers studying Bronze Age activity at the site of Ra’s al‐Jinz 2 suggested that the occupants of the site were fishing to create a surplus of food that may have been exchanged inland or preserved for use as a stable food source throughout the year (Azzarà & de Rorre, : 20–21). The evidence from Saruq al‐Hadid undoubtedly reinforces this hypothesis and goes further, demonstrating that cormorant and dugong were also involved in the movement of marine resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore highly likely that the game meat, pre‐processed hides and horn gathered at Saruq al‐Hadid could similarly have been transported to other sites around the region where its use would be archaeologically “invisible” (Crabtree, ) due to the absence of skeletal remains from the animals. Such an archaeologically invisible movement of resources is hypothesised for the Umm an‐Nar period site of Ras al‐Jinz 2; researchers there have uncovered evidence that fish was being boned, salted and smoked at this coastal site and they suggest that the fillets could have been transported to inland sites (Azzarà & de Rorre, : 11).…”
Section: Discussionmentioning
confidence: 99%
“…| 317 AZZARÀ made of rammed earth, associated with mortared stonework (Azzarà & De Rorre, 2018). As for siting techniques and layout works, the plans of the architectures show a clear variation in the passage between Period III and IV and, conversely, consistency of techniques between Periods II and III (see above) (Azzarà, 2015: 309-316;Azzarà & De Rorre, 2018: 20-22).…”
Section: Evolution Of Architecture During the Eba: The Site Of Ras mentioning
confidence: 99%